Phoenix Company and Tax Crimes: An Analysis of Administrative Penal Law as a Model of Law Enforcement - Febrian Halomoan; Handoyo Prasetyo; Slamet Tri Wahyudi (Journal of Law Perspectives Review, 2026)
This study examines the misuse of tax facilities through the Phoenix Company scheme and analyzes the application of administrative penal law as a law enforcement model in Indonesia's taxation system. The research is normative legal research employing statute and comparative approaches, supported by secondary data from legislation, literature, and relevant legal documents. The findings reveal that the Phoenix Company practice is a form of tax avoidance that exploits regulatory gaps, particularly in the application of final income tax for small and medium enterprises (SMEs). Through strategies such as firm-splitting and income bunching, taxpayers artificially maintain their turnover below the threshold to benefit from lower tax rates, despite operating as a single economic entity. This practice distorts tax fairness, reduces state revenue, and undermines the effectiveness of fiscal policy. Furthermore, the study finds that Indonesian tax law does not explicitly regulate illegal phoenix activities, resulting in enforcement relying on general provisions and principles such as substance over form. In this context, the administrative penal law approach offers a balanced framework by prioritizing administrative sanctions to restore state losses while retaining criminal sanctions as a last resort (ultimum remedium). The study suggests strengthening regulatory frameworks, enhancing inter-agency coordination, and optimizing data integration systems to improve detection and enforcement.